2005
DOI: 10.1111/j.1600-0447.2005.00612.x
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory open‐label trial of aripiprazole as an adjuvant to clozapine therapy in chronic schizophrenia

Abstract: This combination may be useful for clozapine-associated medical morbidity and must be studied in placebo-controlled double-blind randomized trials to determine efficacy and safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
1
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(78 citation statements)
references
References 32 publications
(27 reference statements)
5
67
1
5
Order By: Relevance
“…The relationship between adjunctive medications in clozapine-treated pediatric subjects and adverse metabolic side effects has not been adequately examined in pediatric subjects. There are some preliminary data in adults with schizophrenia that show the addition of aripiprazole to clozapine may be associated with a significant decrease in weight, BMI, fasting total serum cholesterol, and total triglycerides (Henderson et al 2006). Thus, this strategy needs to be explored in pediatric cases as it may target both clozapine-associated medical morbidity and residual symptoms.…”
Section: Week 12 a Week 24mentioning
confidence: 99%
“…The relationship between adjunctive medications in clozapine-treated pediatric subjects and adverse metabolic side effects has not been adequately examined in pediatric subjects. There are some preliminary data in adults with schizophrenia that show the addition of aripiprazole to clozapine may be associated with a significant decrease in weight, BMI, fasting total serum cholesterol, and total triglycerides (Henderson et al 2006). Thus, this strategy needs to be explored in pediatric cases as it may target both clozapine-associated medical morbidity and residual symptoms.…”
Section: Week 12 a Week 24mentioning
confidence: 99%
“…The first of these was an open-label study of aripiprazole 15-30 mg daily added to clozapine (mean dose 455 mg/day) for 6 weeks in 13 people with chronic schizophrenia (Henderson et al, 2006). Eight people completed the trial and two withdrew at week 4.…”
Section: Use Of Adjunctive Aripiprazolementioning
confidence: 99%
“…68 We identified six noncontrolled observational studies that examined the relationship between antipsychotic polypharmacy and clinical outcomes in samples without documented treatment resistance to monotherapy (Table 2). [71][72][73][74][75][76] One study did not report on clinical outcomes. 71 Three of the studies evaluated the addition of a second antipsychotic to an existing antipsychotic 72,74,75 ; two studies found no improvement in symptoms, 72,75 while one study reported no clinical effects.…”
Section: Samples Without Established Treatment Resistance To Antipsycmentioning
confidence: 99%
“…[71][72][73][74][75][76] One study did not report on clinical outcomes. 71 Three of the studies evaluated the addition of a second antipsychotic to an existing antipsychotic 72,74,75 ; two studies found no improvement in symptoms, 72,75 while one study reported no clinical effects. 74 The remaining two studies had a different design, using regression analysis to assess the association between antipsychotic polypharmacy and premature death in patients with schizophrenia.…”
Section: Samples Without Established Treatment Resistance To Antipsycmentioning
confidence: 99%
See 1 more Smart Citation